Structural synthesis of ancient Chinese foot-operated silk-reeling mechanism - Hsiao, Kuohung; Chen, Yuhsun; Yan, Hongsen (Frontiers of mechanical engineering in China, 2010)
This work synthesizes the structures of the foot-operated silk-reeling mechanism, which was vaguely depicted in many literatures in ancient China. Based on the analysis of the mechanism, the structural characteristics and design constraints of the mechanism with indeterminate links and joints are concluded. Then, according to the concepts of generalization and specialization subject to the concluded design constraints, all feasible structures of the mechanism that met the technological standards of the subject’s time period are reconstructed. This reconstruction process provides a logical foundation to better understanding, clarification, and suggestions for the issue of ancient mechanical drawings with indeterminate links and joints.